PENGARUH NILAI INVESTASI, NILAI UPAH, DAN NILAI PRODUKSI TERHADAP PENYERAPAN TENAGA KERJA PADA INDUSTRI MEBEL DI KECAMATAN PEDURUNGAN KOTA SEMARANG - Riky Eka Putra (Economics Development Analysis Journal, 2012)
One attempt to increase employment opportunities is through the development in the industrial sector, because the industrial sector has great potential in energy absorption kerjan. In the District of Semarang Pedurungan furniture industry to contribute in terms of labor absorption, but absorption of labor disproportionate to the value of investment, wages and production value. Factors that affect employment is an investment, the value of wages and production value. The population in this study were 31 employers in the furniture industry Pedurungan Semarang District as well as a sample. Variable is the value of research investment, wages, value of production as the independent variable and the employment as the dependent variable. Data collection methods taken by the method of documentation, questionnaires and interviews or questionnaires. Data analysis methods are multiple linear regression analysis with the program were analyzed using SPSS 16 for windows. The results of regression analysis showed that partially or simultaneously have a significant effect Atara investment value, value of production and wages and the value of the furniture industry employment in the District Pedurungan Semarang. Based on the results obtained by regression analysis of R square value of 0.777 which indicates that the influence of investment value, the value of wages and the value of production and employment in the furniture industry Pedurungan Semarang District of 77.7% and 22.3% influenced by other variables that are not incorporated into the model. From the research we can conclude that there are positive effects of investment value, the value of wages and the value of production on employment in the furniture industry in the District Pedurungan Semarang. See this then you should 1. Employers can increase investment if the firm’s profit more than 50%. 2. Employers can increase labor costs if the firm’s profit more than 50%. 3. Employers can increase production if the value of the firm’s profit more than 50%. Pedurungan District of Semarang City.